Tamoxifen Retinopathy: Retinal cavitation without crystalline deposits - Bhakhri, Raman; Jiang, Leo; Merchant, Nitasha; Brady, Brittney (Canadian Journal of Optometry, 2023)
Tamoxifen is a selective estrogen receptor modulator commonly used to treat and prevent the recurrence of estrogen receptor-positive breast cancer. Even at low doses, adverse effects have been reported such as pseudo cystic foveal cavitation, refractile crystalline deposits, and photoreceptor disruption. With the advent of modern imaging technology such as optical coherence tomography, the prevalence of tamoxifen retinopathy has been found to be greater than previously published reports. We report a case of tamoxifen retinopathy, that manifested without typical crystalline retinal deposits and a normal fundus exam, with a diagnosis being made based on clinical findings, risk factors, and multimodal imaging. A comprehensive review of the condition is also presented including pathophysiology, treatment, and multimodal imaging results.